Indonesian Capital Market Reaction to The Increase of Tobacco Product Excise Rate in Indonesia - Amalia, Mila; Ardiansari, Anindya (Management Analysis Journal, 2021)
The purpose of this research is to analyze the reaction of capital market by conducting research about the differences of abnormal returns, trading volume activity and security return variability before and after the increase in the Tobacco Excise rate on January 1, 2020 and February 1, 2021. This research uses an event study approach, the sample used in this research are 4 companies. Sampling was done by purposive sampling method. This study uses secondary data sources with a quantitative approach. The results of this research showed that the capital market reacts to the increase in the Tobacco Excise rate on January 1, 2020 and February 1, 2021. Based on the results of the different tests, the average abnormal return and the average trading volume activity in the period before and after the event shows that there is a significant difference, while for the different test results, the average security return variability shows that there is no significant difference in the seven days before and seven days after the increase in Tobacco Excise on January 1, 2020 and February 1, 2021.